Design of a neutron shielding performance test system base on Am–Be neutron source. (April 2022) - Zhao, Dong; Jia, Wenbao; Hei, Daqian; Cheng, Can; Li, Jiatong; Cai, Pingkun; Chen, Yize
Abstract: A system for neutron shielding performance test was designed based on an Am–Be neutron source and 3 He proportional counter. The Am–Be neutron source was shielded by paraffin wax block with a thickness of dozens of centimeters and collimated by polyethylene rod. The neutron energy spectra in front of the collimator were simulated by MCNP. The detector system was designed based on 3 He proportional counter and different response tuning assembly (RTA) to optimize the neutron energy region of interest. A method for testing neutron shielding performance for thermal, epithermal, fast neutrons and neutron ambient dose equivalent rate was proposed by employing different response tuning assembly (RTA). Common radiation shielding materials including polyethylene (PE), borated polyethylene (BPE) and graphite were conducted with the designed system. The results demonstrated that the proposed method is efficient for investigating the neutron shielding performance of materials. Highlights: A convenient shielding property test method for neutrons of different energies was proposed. He-3 detector's response for different energy neutrons was simulated by MCNP 5. Response tuning assembly can optimize the detector's neutron energy region of interest. Benchmark experiments and simulations for polyethylene, borated polyethylene and graphite were completed.